ONLINE PEER TEACHING WITH PROBLEM BASED LEARNING: THE EFFECT FOR STUDENTS’ MATERIALS UNDERSTANDING AS A TEACHER CANDIDATES - Maghfira Febriana; Ika Yunita Nurkholifah (UICELL, 2021)
This research is an experimental study with one group pre-test - post test design. This study purpose was to determine the effect of the application of online peer teaching with a problem based learning model for understanding material of students as a teacher candidate. The subjects in this study were students of 2nd Semester Tadris Mathematics Program year 2020. The data of this research was collecting by pre-test and post test. The value data was calculated using Wilcoxon non-parametric statistics by using SPSS. The hypothesis given is alternative hypothesis (Ha): there is a difference in the results of the pre-test and post test, and null hypothesis (Ho): there is no difference in the results of the pre-test and post test. Based on the calculation results obtained, it shows the value of asymp.sig. (2-tailed) = 0.000 with a significance level of 5% (0.05) because the value of 0.000 is smaller than 0.05, so it is concluded that "Ha is accepted". It means that there is a difference between the results of the pre-test and post test, so it can be concluded there is a significant effect of the use online peer teaching with problem based learning on the understanding of materials students as a teacher candidates. Keywords: peer teaching, problem-based learning, materials understanding